Rampant Land Dispute Cases - Nasution, Sari Dewi; Br. Sembiring, Tamaulina (Ipso Jure, 2024)
This research examines the problem of land disputes in Indonesia caused by the illegal practices of the land mafia and poor land management by housing developers. Based on the Seven Principles of Agrarian Law, land should be used to benefit the community. However, facts on the ground show that much land is controlled unilaterally by the land mafia. They used various methods, including making fake letters and cultivating empty land to sell at high prices. This has led to many ownership disputes and legal problems for legitimate landowners and defrauded buyers. To avoid this problem, the public is advised to process the legality of their land certificates through the National Land Agency (BPN). The legal basis supporting the importance of land certificates is contained in Article 19 and Article 23 of the Basic Agrarian Law (UUPA) no. 5 of 1960 and Law no. 4 of 1996 concerning Mortgage Rights. This research also highlights the challenge of limited land in Indonesia, which causes the high economic value of land to become an object of competition. Housing developers often face land management problems, resulting in land certificates being mortgaged at banks and losses for consumers. The importance of public awareness of checking the completeness and validity of documents before carrying out a house purchase transaction is emphasized to avoid problems in the future. Education and supervision from the government and related institutions, such as BPN, are critical in protecting consumer rights and ensuring legal certainty.